Una retórica de la inmediatez: los Diarios de Gerardo Gandini - Pablo Fessel (Resonancias, 2014)
Gerardo Gandini (1936-2013) developed since the late 60s a musical poetics which main attribute rests on the aesthetical availability of the materials provided by the history of Western music. The reinterpretation of materials coming from different historical contexts shaped Gandini's work as a complex intertextual framework. The availability principle was also extended to all kinds of aesthetic genres. His Diaries project the literary diary and the cycle of pieces, intertwining musical, literary and pictorial imaginaries. The article studies the Diaries by Gandini with the focus posed on: a) empirical aspects related to dating and work's constitution problems; b) the ways his intertextual poetics assume compositional shape –to that end two pieces, "... pájaro profeta (I)" (Diary III) and "Fontana: modelo" (Diary IV), are thoroughly analyzed; c) the aesthetical problems that poses the genre adscription, implied in the works' title as well as in the production and reception conditions of these pieces; and finally, d) several layers of meaning resulting from these aspects.